2021
DOI: 10.2217/bmm-2020-0728
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of DNAJA1 ( Hdj2 ) Predicts Unfavorable Survival Outcomes in Breast Cancer

Abstract: Aim: DNAJA1 is associated with several cancers, but its biomarker potential in breast cancer is not adequately known. Materials & methods: Q-RT-PCR, immunohistochemistry, COBRA methods and in silico tools (KM-Plotter, UALCAN) were used to analyze the expression level, methylation status and prognostic value of DNAJA1 in breast cancer. Results: DNAJA1 expression was significantly higher in clinical tumor samples compared with normal samples. High DNAJA1 mRNA expression is associated with poor survival value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…30 DNAJA1 accumulates unfolded mutp53 in HNSCC cells and promotes tumor metastasis. 31 By using a variety of assays, Ileri et al 32 demonstrated that DNAJA1 expression in clinical tumor tissues was significantly higher than in normal tissues and that high DNAJA1 mRNA expression was associated with low survival in breast cancer. NDRG3 has been implicated in many types of cancer and is a member of the NDRG family.…”
Section: Discussionmentioning
confidence: 99%
“…30 DNAJA1 accumulates unfolded mutp53 in HNSCC cells and promotes tumor metastasis. 31 By using a variety of assays, Ileri et al 32 demonstrated that DNAJA1 expression in clinical tumor tissues was significantly higher than in normal tissues and that high DNAJA1 mRNA expression was associated with low survival in breast cancer. NDRG3 has been implicated in many types of cancer and is a member of the NDRG family.…”
Section: Discussionmentioning
confidence: 99%
“…DNAJA1 , a member of J-domain containing proteins or heat shock protein 40, is evidenced to prevent unfolded mutp53 from proteasomal degradation, which is associated with several cancers. 24,25 It was found that DNAJA1 promoted tumor metastasis by accumulating unfolded mutp53. 26 TAGLN is a regulator of the actin cytoskeleton, and affects the survival, migration, and apoptosis of various cancer cells to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…In this present study, we identi ed 3 prognostic biomarkers of malignant tumor cells in the WT tissue, including DNAJA1, TAGLN, and NES. DNAJA1, a member of J-domain containing proteins or heat shock protein 40, is evidenced to prevent unfolded mutp53 from proteasomal degradation, which is associated with several cancers [17,18]. It was found that DNAJA1 promoted tumor metastasis by accumulating unfolded mutp53 [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is responsible for many cell activities, such as unfolding misfolded protein, polypeptide chain folding, transmembrane transport of polypeptide, assembling and disassembling protein complex, and regulation of protein formation [ 13 , 14 ]. In recent years, emerging in tumor-related fields, DNAJA1 has been identified as biomarker for pancreatic cancer and breast cancer [ 12 , 15 ]. DNAJA1 promotes cancer metastasis through interaction with mutant p53 in head and neck squamous cell carcinoma [ 16 ] and enhances the radiotherapy resistance of glioma cells [ 17 ].…”
Section: Discussionmentioning
confidence: 99%